Implementation of the Waterfall Method in Designing a Health Center Information System - Andriansyah, Andriansyah; Nurhayani, Nurhayani; Jony, Jony (Jurnal Ilmu Komputer dan Informatika, 2025)
Information systems develop along with the rapid development of information technology and have proven to play a role in various activities, such as storing, managing and distributing information by creating a website in its application. Puskesmas is a health service with the aim of providing basic health services to the community, and providing socialization about health. The problem that occurs is how the results of the application of the data collection method on the design of the puskemas information system and how the application of the implementation of the waterfall method designs a website-based puskesmas information system. the results of data management obtained by the puskesmas information system there are 4 processes consisting of profile data management, doctor data management, service data management, user data management. The application of the waterfall method in designing a web-based puskesmas information system can solve problems that occur and provide solutions in disseminating information quickly and accurately to the community. The design of the puskesmas information system has five (5) main designs, namely: 1). The system can display the visitor page when the visitor activates the application on the browser, 2). The system can receive and process data when the user performs CRUD (create, Read, Update, Delete) actions, 3). The system can verify login data and display an error message if the user enters the wrong login data, 4). The system can add